2015
DOI: 10.1021/jp511973k
|View full text |Cite
|
Sign up to set email alerts
|

Optical, Vibrational, and Structural Properties of MoS2 Nanoparticles Obtained by Exfoliation and Fragmentation via Ultrasound Cavitation in Isopropyl Alcohol

Abstract: Thin sheets and small MoS 2 nanoparticles have been obtained by exfoliation/fragmentation processes via intense ultrasound cavitation in isopropyl alcohol (IPA). The formation mechanism, the structure (in terms of size, presence of defects, lattice periodicity) and the optical and vibrational properties of the obtained materials have been investigated by means of atomic force (AFM) and high-resolution transmission electron (HRTEM) microscopies and UV−visible near infrared (UV−vis−NIR) and diffuse reflectance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 69 publications
10
95
0
Order By: Relevance
“…Figure 2c shows a single crystalline MoS 2 cluster with a single set of diffraction spots corresponding to the (100) plane with 0.26 nm spacing. The regular honeycomb pattern shown here originates from the atomic arrangements of Mo and S atoms, which is in agreement with the TEM studies on the MoS 2 nanoparticles made by other methods, e.g., CVD and exfoliation [33,34]. The intensity profile shows this cluster consists of two, non-identical hexagonal layers; the brighter region in the middle has a bi-layered structure with mono-layer structures on both sides.…”
Section: Resultssupporting
confidence: 90%
“…Figure 2c shows a single crystalline MoS 2 cluster with a single set of diffraction spots corresponding to the (100) plane with 0.26 nm spacing. The regular honeycomb pattern shown here originates from the atomic arrangements of Mo and S atoms, which is in agreement with the TEM studies on the MoS 2 nanoparticles made by other methods, e.g., CVD and exfoliation [33,34]. The intensity profile shows this cluster consists of two, non-identical hexagonal layers; the brighter region in the middle has a bi-layered structure with mono-layer structures on both sides.…”
Section: Resultssupporting
confidence: 90%
“…The correlation between solution absorbance and suspension concentration allow for the estimation of sedimentation rate by the change in absorbance over time. 31 From the data in Figure 7d it is evident that suspensions in ACN sediment at a substantially greater rate than in NMP and that WS 2 and MoSe 2 demonstrate significant sedimentation over the 2 minute deposition period compared with NMP. We find that the magnitude of change in sticking factor values is directly related to the degree of sedimentation with more heavily sedimenting particles producing smaller sticking factor values.…”
Section: Resultsmentioning
confidence: 87%
“…Meanwhile, MoS 2 nanomaterials with various morphologies such as open-ended nanotubes [9], hollow nanospheres [2], flower-like microspheres [10], nanorods [11] and nanoparticles [12] have been reported. Among various morphologies, MoS 2 nanoparticles are promising due to their distinct physicochemical properties different from bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that MoS 2 nanoparticles show excellent shock-absorbing performance under a very high shock wave pressure [13] and ultra-low friction and wear [14]. In addition, MoS 2 nanoparticles exhibit enhanced catalytic [3], electronic [15] as well as optical [12] properties. As a result, it is essential to synthesize MoS 2 with a nanoparticle morphology in a controlled manner.…”
Section: Introductionmentioning
confidence: 99%